2000
DOI: 10.1161/01.atv.20.5.1374
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Production by Fibroblasts in Response to Factor VIIa Binding to Tissue Factor Involves Thrombin and Factor Xa

Abstract: Tissue factor (TF) assembled with activated factor VII (FVIIa) initiates the coagulation cascade. We recently showed that TF was essential for FVIIa-induced vascular endothelial growth factor (VEGF) production by human fibroblasts. We investigated whether this production resulted from TF activation by its binding to FVIIa or from the production of clotting factors activated downstream. Incubation of fibroblasts with a plasma-derived FVIIa concentrate induced the generation of activated factor X (FXa) and throm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 39 publications
3
66
3
Order By: Relevance
“…The FVD of Myo grafts, which was higher than that of EC/Fib grafts, was seemingly a result of the large number of small and immature blood vessels, which may have been induced by C2C12-derived angiogenic factors. In parallel, ECs and fibroblasts have also been reported to secrete VEGF (38,39). In line with these works, the addition of ECs significantly promoted flap vascularization and viability after transfer.…”
Section: Discussionsupporting
confidence: 53%
“…The FVD of Myo grafts, which was higher than that of EC/Fib grafts, was seemingly a result of the large number of small and immature blood vessels, which may have been induced by C2C12-derived angiogenic factors. In parallel, ECs and fibroblasts have also been reported to secrete VEGF (38,39). In line with these works, the addition of ECs significantly promoted flap vascularization and viability after transfer.…”
Section: Discussionsupporting
confidence: 53%
“…As noted above, TFPI-2 inhibits the tissue factor VIIa complex (Sprecher et al, 1994;Dvorak, 1987). Tissue factor also upregulated the production of vascular endothelial cell growth factor (Ollivier et al, 1998) and uPAR (Taniguchi et al, 1998) in tumor cells, and its levels perfectly correlated with the degree of tumor angiogenesis and progression in ®brosarcomas, melanomas, breast and pancreatic tumors (Contrino et al, 1996;Mueller et al, 1992;Nakagawa et al, 1998;Mueller and Ruf, 1998). Recently it was reported (Neaud et al, 2000) that human liver myo®broblasts promote in vitro invasion of human hepatocellular carcinoma (HCC) cells through a hepatocyte growth factor (HGF)/urokinase/plasmin-dependent mechanism.…”
Section: Discussionmentioning
confidence: 94%
“…Other studies have implicated the tissue factor VIIa complex in the promotion of tumor progression (Dvorak, 1987;Ruf and Mueller, 1996;Shoji et al, 1998). Speci®cally, tissue factor e ects on tumor angiogenesis and metastasis required it to be in complex with the catalytically active factor VIIa (Ollivier et al, 1998). As noted above, TFPI-2 inhibits the tissue factor VIIa complex (Sprecher et al, 1994;Dvorak, 1987).…”
Section: Discussionmentioning
confidence: 98%
“…It does not demonstrate any structural similarity to either the IFNs or IL-10. Nevertheless, recent reports implicate induction of certain biological activities in cells after binding of FVIIa to TF, suggesting the existence of signal transduction events (Bromberg et al, 1995;Pendurthi et al, 1997;Ollivier et al, 1998;Poulsen et al, 1998;Cunningham et al, 1999;Camerer et al, 1999). While, there is no data demonstrating direct activation of the Jak-Stat pathway by TF:FVIIa complex, cells transfected with a reporter gene under control of the IFN-ginducible promoter responded to FVIIa treatment by upregulation of reporter gene expression, although the authors suggested that MAP kinase activation was responsible for FVIIa-induced transcription of a reporter gene (Figure 3) (Poulsen et al, 1998).…”
mentioning
confidence: 99%